TRATAMENTO COM NEMATICIDAS DO SOLO DE VIVEIRO PARA PRODUÇÃO DE MUDAS DE FIGUEIRA - Sampaio, Vladimir R.; Moraes, Roberto S.; Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2015)
TRATAMENTO COM NEMATICIDAS DO SOLO DE VIVEIRO PARA PRODUÇÃO DE MUDAS DE FIGUEIRA